INFLUENCE OF PRIOR KNOWLEDGE OF YORUBA FIGURATIVE LANGUAGE ON STUDENTS’ ACADEMIC PERFORMANCE IN LITERATURE-IN-ENGLISH - DAVID AYINDE (Gema Cendekia Institute, 2026)
This study sought to investigate the influence of prior knowledge of Yoruba figurative language in the academic performance of student in Literature-in-English in Lagos State. In carrying out study, three research questions were raised. The sample consisted of fifty (50) teachers from twenty (20) secondary schools in Agege Local government Area of Lagos State. The instrument used for data collection was a self-developed questionnaire. The data obtained were analysed using sample mean. The study found out that there is significant influence of prior knowledge of Yoruba figurative language on students' academic performance in Literature-in- English. Also, there is significant relationship between Yoruba figurative language and Literature-in-English. Based on the findings of the study it was recommended that students learn and remember new information best when it is linked to relevant prior knowledge. Hence, prior knowledge of Yoruba figurative language can help the improvement of students' academic performance in literature -in-English.